Analisis Penerapan Safety Risk Management pada Tools Store dan Ground Support Equipment di PT. Mulya Sejahtera Technology - Iwan Engkus Kurniawan; Didin Falahudin; Hari Kurniawan (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2022)
This study analize the safety risk assessment in tools store and ground support equipment at PT. Mulya Sejahtera Technology. As Approved Maintenance Organization (AMO) or provider of aircraft maintenance listed on ministry of transportation, both the area are important related to the handling of a aircraft in an apron and supporting the maintenance of aircraft. The methodology used namely descriptive and qualitative. Begins with identification hazard of any process work relating to tools store and ground support equipment, assess the risk of the hazard associated with the severity and the probability. Then the determination of mitigating steps from potential hazard has been done, so that the risk of the potential hazard can be reduced to acceptable level. The result analysis found 20 hazards with risk assessment as follows: 6 high risk, 8 medium high risk and 6 medium risk. Mitigating steps suggested that the procurement of several facilities related to safety, socialization, training and a briefing against operational personnel.